Faktor-Faktor Penentu Produktivitas Penelitian Dosen sebagai Implementasi Integritas Profesi - Margaretha, Meily; Saragih, Susanti (Zenit, 2012)
This research tried to test the influence of individual attributes (age, gender, academic rank and job tenure); the influence of personal motivational factors that drive academic research (intrinsic and extrinsic factors); the influence of university attributes (organizational support) towards research productivity of lectures in Indonesia. Data were collected through questionnaires to 135 lecturers from private and public universities in Indonesia. From seven hypotheses tested in this research, only the fourth hypothesis was supported. Implications managerial that can be applied in this research are improving organizational culture and climate that support research productivity in the university with the attention to investment factors or extrinsic factors; consumption factors or intrinsic factor; organizational supports such as amount of assistant from students helping lecturers in the research, procedures for propose the research and the total amount needed for the research, the availability of literatures in the library, and the adjustable teaching load for lecturers.  Keywords:  research productivity, consumption factors, investment factors, organizational support